Інформаційна безпека держави в умовах обмежень прав і свобод громадян у період воєнного стану - Ягодзінський, Сергій Миколайович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The issue of implementing the state’s information security strategy under the conditions of political, economic, social, and legal restrictions on the rights and freedoms during a state of war is investigated. The author synthesizes the experience of managing channels on the social media platforms TikTok, Telegram, and YouTube. Principles of administering Internet resources that alleviate social tension and conflicts typical of a state of war are proposed. These principles include: the principle of informational objectivity; the principle of a personal approach to content; the principle of updating public awareness; the principle of cultivating ideas of Victory and Peace; the principle of supporting the Armed Forces of Ukraine; the principle of interethnic and interfaith neutrality; the principle of political intersubjectivity; and the principle of individualization of citizens’ value orientations.